2001
DOI: 10.1093/ndt/16.12.2357
|View full text |Cite
|
Sign up to set email alerts
|

Longer duration of predialysis nephrological care is associated with improved long‐term survival of dialysis patients

Abstract: This study provides suggestive evidence that longer duration of regular nephrological care in the predialysis period, at least for several years prior to the start of dialysis, is associated with a better long-term survival on dialysis. Such data strongly support the argument for early referral and regular nephrological care of chronic renal failure patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
121
3
7

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(140 citation statements)
references
References 21 publications
7
121
3
7
Order By: Relevance
“…We believe this trend is not due to a lack of nephrologists (19). Lack of awareness on the part of patients, their family members, and their physicians (including general practitioners, cardiologists, and diabetologists) about the benefits of regular nephrological care may explain this trend (21). Most members OR, odds ratio; CI, confidence interval; SBP, systolic blood pressure; DBP, diastolic blood pressure; SCr, serum creatinine; BMI, body mass index.…”
Section: Discussionmentioning
confidence: 99%
“…We believe this trend is not due to a lack of nephrologists (19). Lack of awareness on the part of patients, their family members, and their physicians (including general practitioners, cardiologists, and diabetologists) about the benefits of regular nephrological care may explain this trend (21). Most members OR, odds ratio; CI, confidence interval; SBP, systolic blood pressure; DBP, diastolic blood pressure; SCr, serum creatinine; BMI, body mass index.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies 56,111,[119][120][121][122][123] met the inclusion and exclusion criteria, and were included in the review; their characteristics are summarised in Table 10. We did not find any randomised or controlled trials.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Awareness of CKD remains unacceptably low, despite recent attempts to increase awareness through dissemination of clinical practice guidelines and recommendations for patients with CKD or its risk factors to providers [20][21][22], including community awareness events such as World Kidney Day [23,24]. Earlier recognition of CKD can slow the progression of CKD, prevent complications, and reduce cardiovascular-related outcomes; additionally, early referral to a nephrologist has been shown to improve outcomes for those who progress to end-stage renal disease [27][28][29][30]. It has been observed that physicians other than nephrologists are less …”
Section: Introductionmentioning
confidence: 99%